(untitled) (Huellas, 2018)
As historical reality, capitalism has constructed, over time, practices and notions of space that prioritize, naturalize and legitimate private property. However, this perspective is in tension with other ways of thinking and making social life that re-signify space as a common property and as a place to be inhabited collectively. From the point of view of a theoretical and methodological conception within the perspective of critical geography, with contributions from other disciplines (political philosophy, legal history and cultural studies) and a methodology that combines collaborative ethnographic and institutional analysis, this article explorespractices and meanings regarding the use of space in cooperation with a network of organizations known as “Movement ofSelf-managed Workers” in Rosario, in the province of Santa Fe, Argentina. Our aim is to make visible the ways in which participants make use of and decide over spaceto interpret the meanings and practices that arise, since they differ from the ways proposed by the capitalist conceptual and practice framework.